Multicultural psychoeducational assessment - Grigorenko, Elena L. (IG library, 2009)
A very useful resource, not only for psychologists and education professionals, but universally, for all those experts interested in multicultural assessment.". --Heikki Lyytinen, PhD. Professor of Developmental Neuropsychology. University of Jyvaskyla, Finland. This volume provides a thorough and provocative examination of how different cultures measure intelligence and skill, why they use the tools they use, and how their assessment methods are changing in the globalizing world. The contributors discuss the extent to which methods of assessment are limited and culture-bound.